High richness and spatio-temporal turnover of insects in urban environments: A case in a Latin American capital - Aponte, Héctor; Aliaga-Barrera, Diego; Carrera, Candy; Obando, Rafael (Revista de Biología Tropical, 2025)
Introduction: Urban ecosystems are spaces in the city that provide ecosystem services and house a wide diversity of species. One of the key components that maintain different types of processes is insects. Objective: To characterize insect communities in four parks in a district of Lima by analyzing their composition and structure in two seasons of the year. Methods: For this evaluation, two samplings (winter and summer) were carried out using four traps (pitfall, canopy malaise, ground-level malaise, and night trap). Results: The results show a) a high richness with 191 registered morphospecies, grouped into 12 orders and 8 functional groups; b) a low similarity between parks (less than 40 % for the Jaccard index), which reveals a high spatial turnover; c) differences in community composition between winter and summer (temporal turnover), with greater richness and abundance of individuals in the warm season (139 morphospecies and 1 214 individuals, versus 105 morphospecies and 731 individuals for summer and winter respectively) and d) the variation of functional groups at both times of the year. Conclusion: The results show a high diversity and invite us to continue the study of insect diversity in urban ecosystems on a broader scale. Information Decision-makers must be considered this to implement measures that allow maintaining this richness of species in a framework where citizens can value and get benefits by the important role of these organisms in the city.